Sie sind auf Seite 1von 54

CHAPTER 4

4.1

66

(a) T 1 = B'C, T 2 = A'B, T 3 = A + T 1 = A + B'C, T 4 = D T 2 = D (A'B) = A'BD' + D(A + B') = A'BD' + AD + B'D F 1 = T 3 + T 4 = A + B'C + A'BD' + AD + B'D With A + AD = A and A + A'BD' = A + BD':

F 1 = A + B'C + BD' + B'D Alternative cover: F 1 = A + CD' + BD' + B'D

F 2 = T 2 + D' = A'B + D'

 ABCD T 1 T 2 T 3 T 4 F 1 F 2 0000 0 0 0 0 0 1 0001 0 0 0 1 1 0 0010 1 0 1 0 1 1 0011 1 0 1 1 1 0 0100 0 1 0 1 1 1 0101 0 1 0 0 0 1 0110 0 1 0 1 1 1 0111 0 1 0 0 0 1 1000 0 0 1 0 1 1 1001 0 0 1 1 1 0 1010 1 0 0 1 1 1 1011 1 1 0 1 1 0 1100 0 0 1 0 1 1 1101 0 0 1 1 1 0 1110 0 0 1 0 1 1 1111 0 0 1 1 1 0 CD C 00 01 11 10

AB

A

00

01

11

10

M 0
M 1
M 3
M 2
1 1
M 4
M 5
M 7
M 6
1 1
1 1
M
M 12
M 13
15
M 14
1 1
M 8
M 9
M
11
M 10
1 1

D

F 2 = A'B + D'

B

A

CD
C
00
01
11
10
M 0
M 1
M 3
M 2
00
1
1 1
M
M 5
M
M 6
4
7
01
1
1
M
M
12
M 13
15
M 14
11
1
1
1
1
M 8
M 9
M 11
M 10
10
1 1
1
1

D

B

F 1 = A + B'C+ B'D + BD'

B

D

F 1 = A + CD' + B'D + BD'

67

 4.2 F(A, B, C, D) = ((A′D)′ (A′ + BC))′ = A′D + (A′ + BC)′ = A′D + A (BC)′ = A′D + AB′ + AC′ C 1 (A, B, C, D) = ((A′D) (A′ + BC))′ = (A′D)′ + (A′ + BC)′ = (A + D′) + A (BC)′ = A + D′ + AB′ + AC′ = A (1 + B′ + C′) + D′ = A + D′ 4.3 (a) Y i = (A i S' + B i S)E' for i = 0, 1, 2, 3 (b) 1024 rows and 14 columns 4.4 (a) F(A, B, C) = (0, 1, 2, 7)

Simplified SOP form:

F(A, B, C)

= AC+ AB+ ABC

= A(B+ C) + ABC

= A(BC) + ABC

= A XNOR (BC)

= A (BC)

(b)

F(A, B, C) = (1, 3, 5, 7)

Simplified SOP form:

F(A, B, C) = C C

F

 4.5 x y z A B C 0 0 0 0 1 0 0 0 1 0 1 1 0 1 0 1 0 0 0 1 1 0 1 0 1 0 0 0 1 1 1 0 1 1 0 0 1 1 0 1 0 1 1 1 1 1 1 0 A = (2, 5, 6, 7)
 A = xz + yx′ B = (0, 1, 3, 4, 7) = y′z′ + yz + x′z = (y ⊕ z) + x′z C = (1, 4, 6)

= xz+ xyz

68

69

4.6

 xyz F 000 0 001 0 010 0 011 1 100 0 101 1 110 1 111 1

x

A

y
yz
x
00
01
11
10
m
m
m
m
x
0
1
3
2
0
1 z
y
m
m
m
m
z
4
5
7
6
1
1
1 x
1
y

z

F = xz + yz + xy

module Prob_4_6 (output F, input x, y, z); assign F = (x & z) | (y & z) | (x & y); endmodule

F

4.7

(a)

 ABCD wxyz 0000 0000 0001 0001 0011 0010 0010 0011 0110 0100 0111 0101 0101 0110 0100 0111 1100 1000 1101 1001 1111 1010 1110 1011 1010 1100 1011 1101 1001 1110 1000 1111
CD
C
CD
C
AB
00
01
11
10
00
01
11
10
m
m
m
m
m
m
m
m
0
1
3
2
0
1
3
2
00
00
m
m
m
m
m
m
m
m
4
5
7
6
4
5
7
6
01
01
1
1
1
1
B
m
m
m
m
m
m
m
m
12
13
15
14
12
13
15
14
11
1
1
1 11
1
A
A
m
m
m
m
m
m
m
m
8
9
11
10
8
9
11
10
10
1
1
1 10
1
1
1
1
1
D
D
x = AB' + A'B = A
B
w = A
CD
C
AB
00
01
11
10
m
m
m
m
0
1
3
2
00
1
1
m
m
m
m
4
5
7
6
01
1
1
m
m
m
m
12
13
15
14
11
1
1
A
m
m
m
m
8
9
11
10
10
1
1

D

B

y = A'B'C A'BC' + ABC + AB'C'

=
A'(A
B) + A(B
C)'
=
A
B
C
=
X
C
A
w
x
B
y
C
z
D
CD

AB

00

A

01

11

10

C

 00 01 11 10 m 0 m 1 m 3 m 2 1 1 m 4 m 5 m 7 m 6 1 1 m 12 m 13 m 15 m 14 1 1 m 8 m 9 m 11 m 10 1 1 D D

z = A = y

B
C
D

B

B

70

(b)

module Prob_4_7(output w, x, y, z, input A, B, C, D); always @ (A, B, C, D) case ({A, B, C, D})

 4'b0000: {w, x, y, z} = 4'b0000; 4'b0001: {w, x, y, z} = 4'b1111; 4'b0010: {w, x, y, z} = 4'b1110; 4'b0011: {w, x, y, z} = 4'b1101; 4'b0100: {w, x, y, z} = 4'b1100; 4'b0101: {w, x, y, z} = 4'b1011; 4'b0110: {w, x, y, z} = 4'b1010; 4'b0111: {w, x, y, z} = 4'b1001; 4'b1000: {w, x, y, z} = 4'b1000; 4'b1001: {w, x, y, z} = 4'b0111; 4'b1010: {w, x, y, z} = 4'b0110; 4'b1011: {w, x, y, z} = 4'b0101; 4'b1100: {w, x, y, z} = 4'b0100; 4'b1101: {w, x, y, z} = 4'b0011; 4'b1110: {w, x, y, z} = 4'b0010; 4'b1111: {w, x, y, z} = 4'b0001;

endcase

endmodule

Alternative model:

module Prob_4_7(output w, x, y, z, input A, B, C, D); assign w = A; assign x = A ^ B); assign y = x ^ C; assign z = y ^ D; endmodule

71

72

4.8 (a) The 8-4-2-1 code (Table 1.5) and the BCD code (Table 1.4) are identical for digits 0 – 9.

(b)

 8421 Gray ABCD wxyz 0000 0000 0001 0001 0010 0011 0011 0010 0100 0110 0101 0111 0110 0101 0111 0100 1000 1100 1001 1101
CD

AB

00

A

01

11

10

C

11
10

00 01

 m 0 m 1 m 3 m 2 m 4 m 5 m 7 m 6 m 12 m 13 m 15 m 14 m m 8 9 1 1 m 11 m 10

D

w = AB'C'

CD

AB

00

A

01

11

10

C

11

10

00

01

 m 0 m 1 m m 3 2 1 1 m m 4 5 1 1 m 7 m 6 m 12 m 13 m 15 m 14 m 8 m 9 m 11 m 10 D

y = A'BD' + A'B'D

CD
C
00
01
11
10
m
m
m
m
0
1
3
2
00
m
m
m
m
4
5
7
6
01
1
1
1
1
B
B
m
m
m
m
12
13
15
14
11
A
m
m
m
m
8
9
11
10
10
1
1
D
x = AB'C' + A'B
C
AB CD
00
01
11
10
m
m
m
m
0
1
3
2
00
1
1
m
m
m
m
4
5
7
6
01
1
1
B
B
m
m
m
m
12
13
15
14
11
1
A
m
m
m
m
8
9
11
10
10

D

z = A'C'D + BC'D + A'CD'

4.9

 ABCD a b c d e f g 0000 1 1 1 1 1 1 0 0001 0 1 1 0 0 0 0 0010 1 1 0 1 1 0 1 0011 1 1 1 1 0 0 1 0100 0 1 1 0 0 1 1 0101 1 0 1 1 0 1 1 0110 1 0 1 1 1 1 1 0111 1 1 1 0 0 0 0 1000 1 1 1 1 1 1 1 1001 1 1 1 1 0 1 1 C CD 01 11 10 00 00 m 0 1 m 1 m 3 m 2 1 m 6 1 01 m 4 m 5 m 7 m 12 m 13 m 15 m 14 11 m 9 m 11 m 10 10

AB

A

m
8
1

D

e = A'CD' + B'C'D'

73

CD
C
CD
C
AB
AB
00
01
11
10
00
01
11
10
m
m
m
m
m
m
m
m
0
1
3
2
0
1
3
2
00
1
1
1
00
1
1
1
1
m
m
m
m
m
m
m
m
4
5
7
6
4
5
7
6
01
1
1
1
01
1
1
B
B
m
m
m
m
m
m
m
m
12
13
15
14
12
13
15
14
11
11
A
A
m
m
m
m
m
m
m
m
8
9
11
10
8
9
11
10
10
1
1
10
1
1
D
D

a = A'C + A'BD + B'C'D' + AB'C'

b = A'B' + A'C'D' + A'CD + AB'C'

CD
C
CD
C
AB
AB
00
01
11
10
00
01
11
10
m
m
m
m
m
m
m
m
0
1
3
2
0
1
3
2
00
1
1
1
00
1
1
1
m
m
m
m
m
m
m
m
4
5
7
6
4
5
7
6
01
1
1
1
1
01
1
1
B
B
m
m
m
m
m
m
m
m
12
13
15
14
12
13
15
14
11
11
A
A
m
m
m
m
m
m
m
m
8
9
11
10
8
9
11
10
10
1
1
10
1
1
D
D

B

c = A'B + A'D + B'C'D' + AB'C'

d = A'CD' + A'B' C+ B'C'D' + AB'C' + A'BC'D

CD
C
AB
00
01
11
10
m
m
m
m
0
1
3
2
00
1
m
m
m
m
4
5
7
6
01
1
1
1
m
m
m
m
12
13
15
14
11
A
m
m
m
m
8
9
11
10
10
1
1

D

B

f = A'BC' + A'C'D' + A'BD + AB'C'

CD

AB

00

A

01

11

10

C

11

10

00

01

 m 0 m 1 m m 4 5 1 1 m m 3 2 1 1 m m 7 6 1 m 12 m 13 m 15 m 14 m m 8 9 1 1 m 11 m 10 D

B

g = A'CD' + A'B'C + A'BC' + AB'C'

4.10

 ABCD wxyz 0000 0000 0001 1111 0010 1110 0011 1101 0100 1100 0101 1011 0110 1001 0111 1000 1000 1000 1001 0111 1010 0110 1011 0101 1100 0100 1101 0011 1110 0010 1111 0001
CD
C
CD
C
AB
00
01
11
10
00
01
11
10
m
m
m
m
m
m
m
m
0
1
3
2
0
1
3
2
00
1 1
1 00
1
1
1
m
m
m
m
m
m
m
m
4
5
7
6
4
5
7
6
01
1
1 1
1 01
1
B
m
m
m
m
m
m
m
m
12
13
15
14
12
13
15
14
11
11
1
A
A
m
m
m
m
m
m
m
m
8
9
11
10
8
9
11
10
10
1
10
1
1
1
D
D

B

w = A'(B + C + D) + AB'C'D'

= A
(B + C + D)
CD
C
AB
00
01
11
10
m
m
m
m
0
1
3
2
00
1
1
m
m
m
m
4
5
7
6
01
1
1
m
m
m
m
12
13
15
14
11
1
1
A
m
m
m
m
8
9
11
10
10
1
1
D
y =
CD' + C'D = C
D

x = B'(C + D) + CB'D'

= B
(C + D)
CD
C
AB
00
01
11
10
m
m
m
m
0
1
3
2
00
1 1
m
m
m
m
4
5
7
6
01
1 1
B
B
m
m
m
m
12
13
15
14
11
1 1
A
m
m
m
m
8
9
11
10
10
1 1

D

z = D

74

For a 5-bit 2's complementer with input E and output v:

v = E

(A + B + C + D)

4.11

(b)

(a)

A

3

A 2

A 1

A 0

 x y x y x y x y Half Adder Half Adder Half Adder Half Adder C S C S C S C S

1

Note: 5-bit output

A 3

1

A

2

1

A

1

1

A

0

1

 x y x y x y x y Full Adder Full Adder Full Adder Half Adder B D B D B D B D

75

Note: To decrement the 4-bit number, add -1 to the number. In 2's complement format ( add F h ) to the number. An attempt to decrement 0 will assert the borrow bit. For waveforms, see solution to Problem 4.52.

4.12

 x y Diff. Bout 0 0 0 0 0 1 1 0 1 0 1 1 1 1 0 0

Diff. = xy + xy

x y

= x y

Bout = xy

Bin

Diff.

Bout

 0 0 0 0 0 0 0 1 1 1 0 1 0 1 0 0 1 1 0 0 1 0 0 1 1 1 0 1 0 1 1 1 0 0 0 1 1 1 1 1

Bout = xy+ yBin + xBin

Diff.

= x(y Bin)

+ x (y Bin)

76

= x y Bin

Bout

= (1, 4, 5, 7)

 4.13 Sum C V (a) 1101 0 1 (b) 0001 1 1 (c) 0100 1 0

4.14

4.15

4.16

 (d) 1011 0 1 (e) 1111 0 0 xor AND OR XOR 10 + 5 + 5 + 10

= 30 ns

C 4

S 0

S 1

= C 13 + P 3 C 3

= C 13 + P 3 (C 12 + P 2 C 11 + P 2 P 1 C 10 + P 2 P 1 P 0 C 10 )

= C 13 P 3 C 12 + P 3 P 2 C 11 + P 3 P 2 P 1 C 10 + P 3 P 2 P 1 P 0 C 0

= P 0 C 0

= P 1 C 1

Using S i = P i C i

S

2

= P 2 C 2

S

3

= P 3 C 3

 (a) (C'G' i + p' i )' = (C i + G i )P i = G i P i + P i C i = A i B i (A i + B i ) + P i C i

= A i B i + P i C i = G i + P i C i

= A i B i + (A i + B i )C i = A i B i + A i C i + B i C i = C i+1

4.17

(P i G' i ) C i

(b)

= (A i + B i )(A i B i )'

= (A' i B i + A i B' i )

C i = (A i + Bi)(A' i + B' i )

C i = A i

B i

C i = S i

C i

Output of NOR gate = (A 0 + B 0 )' = P' 0 Output of NAND gate = (A 0 B 0 )' = G' 0

 S 1 = (P 0 G' 0 ) ≈ C 0 C 1 = (C' 0 G' 0 + P' 0 )' as defined in part (a) (a)

(C' i G' i + P' i )' = (C i + G i )P i = G i P i + P i C i = A i B i (A i + B i ) + P i C i

77

= A i B i + P i C i = G i + P i C i

= A i B i + (A i + B i )C i = A i B i + A i C i + B i C i = C i+1

(P i G' i )C i = (A i + B i )(A i B i )'C i = (A i + B i )(A' i + B' i )C i = (A' i B i + A i B' i )C i = A i B i C i = S i

(b)

Output of NOR gate = (A 0 + B 0 )' = P' 0

Output of NAND gate = (A 0 B 0 )' = G' 0

S 0 = (P 0 G' 0 )C 0 C 1 = (C' 0 G' 0 + P' 0 )'

as defined in part (a)

78

4.18

 Inputs Outputs ABCD wxyz 0000 1001 0001 1000 0010 0111 0011 0110 0100 0101 0101 0100 0110 0011 0111 0010 1000 0001 1001 0000

d(A, b, c, d) = (10, 11, 12, 13, 14, 15)

79

CD
C
CD
C
AB
AB
00
01
11
10
00
01
11
10
m
m
m
m
m
m
m
m
0
1
3
2
0
1
3
2
00
1
1
00
1
1
m
m
m
m
m
m
m
m
4
5
7
6
4
5
7
6
01
01
1
1
B
B
m
m
m
m
m
m
m
m
12
13
15
14
12
13
15
14
11
x
x
x
x
11
x
x
x
x
A
A
m
m
m
m
m
m
m
m
8
9
11
10
8
9
11
10
10
x
x
10
x
x
D
D
w = A'B'C'
x = BC' + B'C = B
C
CD
C
00
01
11
10
m
m
m
m
0
1
3
2
00
1 1
m
m
m
m
4
5
7
6
01
1 1
B
B
m
m
m
m
12
13
15
14
11
x
x
x
x
m
m
m
m
8
9
11
10
10
x
x
D
D
y = C
z = D'

4.19

4.20

4.21

B 3

B 2

B 1

B 0

Mode = 0 FOR Add Mode = 1 for Subtract

9's Complementer
(See Problem 4.18)
 Select = 1 Select = 0 Quadruple 2 x 1 MUX
Select
A 3
A 2
A 1
A 0

C in

Combine the following circuit with the 4-bit binary multiplier circuit of Fig. 4.16.
A
C 6
C 5
C 4
C 3
C 2
3
B
B
B
B
3
2
1
0
C
out
Augend
D 7
D 6
D 5
D 4
D 3
D 2

C 1

D 1

Two 4-bit numbers are A 3 A 2 A 1 A 0 and B 3 B 2 B 1 B 0 To Check unequal:

C 0

D 0

80

4.22

4.23

x = (A 3 B 3 ) + (A 2 B 2 ) + (A 1 B 1 ) + (A 0 B 0 )

81

XS-3
Binary
ABCD
wxyz
0011
0000
0100
0001
0101
0010
0110
0011
0111
0100
1000
0101
1001
0110
1010
0111
1011
1000
1100
1001
CD
C
CD
C
AB
AB
00
01
11
10
00
01
11
10
x
m
m
m
m
m 0
m 1
m 3
0
1
3
2
00
x x
00
X
X
X
m
m
m
m
m 4
m 5
m 7
m 6
4
5
7
6
01
01
1
B
B
m
m
m
m
m
m
m 12
m 13
15
14
12
13
15
14
11
1 x
x 11
x
x
x
x
A
A
m
m
m
m
m
m
m 8
m 9
11
10
8
9
11
10
10
1 10
1
1
1
D
D
w = AB + ACD
x = B'C' + B'D' + BCD
y = C'D + CD'
z = D'
D0 = A1'A0' = (A1 + A0)'
D1 = A1'A0 = (A1 + A0')'
(NOR)
D0' = (A1'A0')'
D1' = (A1'A0)'
(NAND)
(NOR)
(NAND)

82

D2 = A1A0' = (A1' + A0)'
D3 = A1A0 = (A1' + A0)'
(NOR)
D2' = (A1A0')'
D0' = (A1A0)'
(NAND)
(NOR)
(NAND)
A
1
D 0 = (A 1 + A 0 + E' )' = A' 1 A' 0 E
A
0
D 1 = (A 1 + A' 0 + E' )' = A' 1 A 0 E
D 2 = (A' 1 + A 0 + E' ) = A 1 A' 0 E
D 3 = (A' 1 + A' 0 + E' )' = A 1 A 0 E
E
E A 1
A 0
D 0 ' = (A 1 + A 0 + E' ) = (A' 1 A' 0 E)'
D 0
D 1 ' = (A 1 + A' 0 + E' ) = (A' 1 A 0 E)'
D 1
D2' = (A 1 ' + A 0 + E' ) = (A 1 A 0 'E)'
D 2
D 3 ' = (A 1 ' + A 0 ' + E' ) = (A 1 A 0 E)'
D 3
 4.24 2421 Decimal [Using Table 1.5] ABCD

0000

0001

0010

0011

0100

1011

1100

1101

1110

1111

D 0 = ABCDD 1 = ACD D 2 = ACDD 3 = ACD D 4 = AB D 5 = ABD 6 = ACDD 7 = ACD D 8 = ACDD 9 = BCD

D

D

D

D

D

D

D

D

D

0

1

2

3

4

5

6

7

8

D9

4.25

4.26

A 0

A 1

A 2

A 3

A 4

E

8
3
x 8
D 0 - D 7
Decoder
E
8
3
x 8
D 8 - D 15
Decoder
E
0
0
2
1
2
x 4
Decoder
2
8
3
x 8
1
2
D 16 - D 23
Decoder
3
E
E
8
3
x 8
D 24 - D 31
Decoder
E

83

0
A 0
2
4
2
x 4
D 0 - D 3
1
Decoder
A 1
2
E
0
2
4
2
x 4
D 4 - D 7
1
Decoder
2
E
0
0
A 2
2
1
2
x 4
Decoder
0
2
2
4
2
x 4
1
A 3
2
D 8 - D 11
1
Decoder
3
2
E
E
E
0
2
4
2
x 4
D 12 - D 15
1
Decoder
2
E

4.27 F 1 (A, B, C) = (2, 4, 6) F 2 (A, B, C) = (3, 5, 7) F 3 (A, B, C) = (0, 2, 3, 4, 7)

84

4.28 F 1 =xy + xz′ + yz′ = (2, 4, 6, 7)
F 2 = xz + xy + yz = (3, 5, 6, 7)
(a)
F 3 = y′z + x′y′z′ + xy =
(0, 1, 5, 6, 7)
(b)
F 1 = z′ + xy = (0, 2, 4, 6, 7)
F 2 = yz + x′y + y′z′ = (0, 2, 3, 4, 7)
F 3 = (x′ + y)z + xy′z = (0, 2, 5, 6)